Komunikasi Persuasif Live Streamer Akun TikTok @avoskinbeauty dalam Meningkatkan Direct Selling - Irawan, Zahra Kesuma; Khohar, Abdul; Yuliani, Magvira (Universitas Batanghari Jambi, 2025)
This research aims to understand the role of persuasive communication of live streamer TikTok account @avoskinbeauty in increasing Avoskin's direct selling. The research method used is a qualitative approach with a case study, involving in-depth interviews with live streamers and live streaming coordinator, as well as analysis on the content of the live streaming session. The AIDDA theory (Attention, Interest, Desire, Decision, Action) was applied as an analytical framework. The results showed that direct selling on the live streaming of the TikTok @avoskinbeauty account for the period February 15, 2025 - February 28, 2025 experienced significant fluctuations due to influence of several factors such as big campaigns, discount subsidies, flash sales, and persuasive communication skills of live streamers.